The sporting lives of Sir Shenton Thomas and the male European internees at Changi Prison camp during the Japanese occupation of Singapore, 1942–1945 - Lim, P.H.; Aman, M.S. (Taylor & Francis, 2015)
During the Japanese occupation of British Malaya and Southeast Asia from the years 1942 to 1945 there were reports of POWs being allowed to play cricket, football, rugby and basketball, as told by Kevin Blackburn in The Sportsmen of Changi published in 2012. This research about the sporting lives of a Governor and male European internees at Singapore’s Changi prison is likely to be first detailed research on this topic. The authors depended mainly on four published diaries and 262 issues of the men’s camp newspaper, Changi Guardian, to account for the male internees’ casual and competitive cricket, football, hockey, volleyball, badminton, tennis and boxing matches that were played during internment. The Japanese Military Administration allowed the male internees to organize their daily lives and play games that they indulged in during the pre-War period as the British dominated the Singapore Cricket Club, Penang Cricket Club and Perak Club. The internees were able to play the various games and matches in spite of the limited food and sparse facilities. Many of the cricket and football games that were played were organized as inter-state, inter-club or league matches. These games were played with improvized equipment and rules.